A reason to eat healthy: The role of meaning in life in maintaining homeostasis in modern society. Issue 1 (23rd February 2016) - Piko, Bettina F; Brassai, Laszlo
Health is a state of homeostasis of four principle kinds, namely, biochemical, physiological, psychological, and social. In this article, we complete this theory with a fifth element, namely, spiritual balance. Existential attitudes have been found to be closely related to identity formation, moral development, value-related attitudes, personal goals, and lifestyle choices. Meaning in life and searching for meaning serve better health since they may encourage people to engage in health-promoting behaviors and avoid health-risking behaviors, such as obesity and eating disorders. The meaning-making model proposes that people's perceptions may contribute to content/discontent with life, body, and the world.